(untitled) (Revista Nacional de Odontología, 2025)
Objective: To strengthen oral hygiene practices for newborns through a health education strategy using a low-cost simulation tool, targeting mothers, caregivers, healthcare professionals, and medical and nursing students. Methodology: The project comprised two educational components: one for mothers of newborns and another for final-year medical and nursing students, as well as healthcare professionals in hospitals with certified delivery rooms. For these groups, educational materials were developed to facilitate oral hygiene education, including a baby simulation kit, a basic concepts booklet, and an instructional guide. Results: The baby simulation kit was used to train 627 nursing and medical students and 172 healthcare professionals from 10 hospitals with certified delivery rooms. Direct support was provided to 1,200 mothers with their newborns, and 15,600 newborn oral hygiene kits were distributed. Conclusions: The baby simulation kit was a well-regarded tool for pre-natal oral hygiene education. It facilitated the integration of dentistry as part of the interdisciplinary healthcare team in various institutions and raised awareness among healthcare professionals regarding the importance of oral care for newborns, thus establishing them as key partners in this endeavor.